The Archaeology of Events : Cultural Change and Continuity in the Pre-Columbian Southeast - O'Donoughue, Jason M., 1979-; Gilmore, Zackary I., 1981- (Book collections on Project MUSE., 2015)
"Across the social sciences, gradualist evolutionary models of historical dynamics are giving way to explanations focused on the punctuated and contingent 'events' through which history is actually experienced. The Archaeology of Events is the first book-length work that systematically applies this new eventful approach to major developments in the pre-Columbian Southeast. Traditional accounts of pre-Columbian societies often portray them as 'cold' and unchanging for centuries or millennia. Events-based analyses have opened up archaeological discourse to the more nuanced and flexible idea of context-specific, rapidly transpiring, and broadly consequential historical 'events' as catalysts of cultural change. The Archaeology of Events, edited by Zackary I. Gilmore and Jason M. O'Donoughue, considers a variety of perspectives on the nature and scale of events and their role in historical change. These perspectives are applied to a broad range of archeological contexts stretching across the Southeast and spanning more than 7,000 years of the region's pre-Columbian history. New data suggest that several of this region's most pivotal historical developments, such as the founding of Cahokia, the transformation of Moundville from urban center to vacated necropolis, and the construction of Poverty Point's Mound A, were not protracted incremental processes, but rather watershed moments that significantly altered the long-term trajectories of indigenous Southeastern societies. In addition to exceptional occurrences that impacted entire communities or peoples, Southeastern archaeologists are increasingly recognizing the historical importance of localized, everyday events, such as building a house, crafting a pot, or depositing shell. The essays collected by Gilmore and O'Donoughue show that small-scale events can make significant contributions to the unfolding of broad, regional-scale historical processes and to the reproduction or transformation of social structures. The Archaeology of Events is the first volume to explore the archaeological record of events in the Southeastern United States, the methodologies that archaeologists bring to bear on this kind of research, and considerations of the event as an important theoretical concept"--